2013
DOI: 10.1002/chem.201202314
|View full text |Cite
|
Sign up to set email alerts
|

S‐Alkylation of Soft Scorpionates

Abstract: The alkylation reactions of soft scorpionates are reported. The hydrotris(S-alkyl-methimazolyl)borate dications (alkyl = methyl, allyl, benzyl), which were prepared by the reaction of Tm(Me) anion and primary alkyl halides, have been isolated and structurally characterised. The reaction is, however, not universally successful. DFT analysis of these alkylation reactions (C=S versus B-H alkylation) indicates that the observed outcome is driven by kinetic factors. Extending the study to incorporate alternative im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Accompanying this difference in THF coordination modes, the [Tm MeBenz ] and [Tm Bu t Benz ] ligands adopt different conformations in their respective sodium complexes. Thus, whereas the [Tm MeBenz ] ligand possesses a 0:3 conformation 9 in which the three thione moieties point away from the B–H group, such that the ligand binds in a κ 3 - S 3 manner, the [Tm Bu t Benz ] ligand adopts an inverted 3:0 conformation in which the three thione moieties point towards the B–H group and the ligand binds in a κ 3 - S 2 H manner.…”
Section: Resultsmentioning
confidence: 99%
“…Accompanying this difference in THF coordination modes, the [Tm MeBenz ] and [Tm Bu t Benz ] ligands adopt different conformations in their respective sodium complexes. Thus, whereas the [Tm MeBenz ] ligand possesses a 0:3 conformation 9 in which the three thione moieties point away from the B–H group, such that the ligand binds in a κ 3 - S 3 manner, the [Tm Bu t Benz ] ligand adopts an inverted 3:0 conformation in which the three thione moieties point towards the B–H group and the ligand binds in a κ 3 - S 2 H manner.…”
Section: Resultsmentioning
confidence: 99%
“…NaTbz was prepared as previously reported. 18 All NMR spectra were recorded on either a Bruker DPX400 or a Bruker AV500 spectrometer. The spectra were referenced to internal solvent peaks and thus to TMS.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed a recent study on the alkylation of benzothiazole-2-thione and thiazolidine-2-thione based soft scorpionates demonstrated that the B-N bond is readily severed in response to S-alkylation. 18 The implication is that as electron density is removed from the heterocycle the B-N bond weakens. For the parent methimazole based species the alkylated nitrogen atom within the ring, which bears a negative charge, can compensate for these changes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed this family of ligands (Tm R ) has since proved to be a rich source of these elusive entities. In complete contrast, our studies with carbon based electrophiles and mild oxidising agents have opened up new avenues in heterocyclic chemistry , . This success with carbon centred electrophiles left silicon as the only member of group 14 to be tested .…”
Section: Introductionmentioning
confidence: 99%